Internationalization of Higher Education: Past and Future - Knight, Jane; de Wit, Hans (International Higher Education, 2018)
Over the past 25 years, internationalization has evolved from a marginal and minor component to a global, strategic, and mainstream factor in higher education. Has international higher education lived up to our expectations and its potential? What values have guided it? What have we learned from the past to guide us into the future? Is the strong appeal for internationalization of the curriculum a return to the former days of cooperation and exchange, or a call for a more responsible process of internationalization? Who could have forecasted that internationalization would transform from a process based on values of cooperation to one that is increasingly characterized by competition?